PENGARUH RETURN ON ASSETS DAN RETURN ON EQUITY TERHADAP HARGA SAHAM PADA PT INDOSAT TBK PERIODE 2013-2022 - Nadya Clarrisha Sompotan; Simangunsong, Ria Rosalia (Publika Citra Media, 2025)
The main objective of this study is to determine the effect of profitability ratios, specifically ROA and ROE, on the stock price of a telecommunications company, PT Indosat Tbk. The research method used is descriptive with a quantitative approach. Based on the study, return on assets (ROA) and return on equity (ROE) do not affect stock prices, with a coefficient of determination value of 0.336, meaning the contribution of the independent variables, consisting of ROA and ROE, to the stock price is 33.6%. The remaining 66.4% is influenced by other variables not included in this study. This is supported by the t-test results, where for X1, t- value is positive 0.795 < t-table value 2.36462 with a significance value of 0.453 > 0.05, and for X2, t-value is negative -0.372 < t-table value 2.36462 with a significance value of 0.721 > 0.05. Thus, H0 is accepted and Ha is rejected. This indicates that there is no significant effect of return on assets and return on equity on stock prices. The results of this study show a negative effect between return on assets and return on equity simultaneously, where the multiple linear regression equation is Y = 4598.038 + 33194.549 X1 + (-3015.343) X2, meaning there is a negative influence. This is confirmed by the hypothesis testing results, where the F- count is 1.772 < F-table value 4.74 with a significance value of 0.238 > 0.05, which means it can be concluded that the variables return on assets and return on equity do not have a significant effect on stock prices.